The Student Experience in Second Year Programmes in New Zealand Law Schools - Lynne Taylor; Erik Brogt; Ursula Cheer; Natalie Baird (Legal Education Review)
Law schools are increasingly responsive to the introduction of animal law into elective offerings. Despite this, some would be animal law educators may still face institutional resistance to the regular inclusion of animal law in law school curricula. This may be truer today in schools outside of the United States, where the subject has yet to reach the same level of acceptance. The ways an animal law unit can be framed through particular disciplinary lenses so as to draw it into alignment with the research strengths, educational goals, and self-identity of a law school may be a means to render the subject more palatable to course administrators. Alignment with the culture and teaching and research strengths of a law school may also enable greater learning opportunities and outcomes for students. One of the qualities of animal law is its pliability to alternative emphases due to the way in which it straddles many different areas of law and jurisprudence, and engages both the public and private spheres. In this paper I explore alternative framings of an animal law subject that might be catered towards the requirements of a law school or teacher in question along these lines.